Back Cover: Functionalization of CeO2(1 1 1) by Deposition of Small Ni Clusters: Effects on CO2 Adsorption and O Vacancy Formation (ChemCatChem 4/2015). Issue 4 (February 2015) - Hahn, Konstanze R.; Seitsonen, Ari P.; Iannuzzi, Marcella; Hutter, Jürg
<x xml:space="preserve">Abstract</x> The cover picture shows the rocky road of cluster stabilization. In their Full Paper on page 625 ff. K. Hahn et al. use density functional theory calculations to simulate the adsorption of small Ni clusters on a CeO2 surface to investigate the fundamental properties of the Ni/CeO2 system relevant in many catalytic applications. Deposition of Ni clusters has been shown to significantly change oxygen vacancy formation properties in CeO2. The article highlighted by this cover can be found on p. 625 ff. of Issue 4, 2015.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>